Pengembangan LKPD Berbasis Model Problem Based Learning (PBL) Pada Materi Larutan Penyangga Siswa Kelas XI SMAN 1 Praya Barat - Zuharah Zuharah; I Noman Loka; Sunniarti Ariani (FKIP University of Mataram, 2025)
This research is a development research or Research and Development (R&D) which aims to produce Student Worksheets (LKPD) that are categorized as minimally feasible and practical regarding the material of buffer solutions. The type of development used is research and development (R&D) which refers to the 4D model. LKPD validation was carried out by two Chemistry Educationlecturers and one Chemistry subject teacher at the high school level, with two main validations, namely material validation and media validation. The validation process uses the Aiken's Index formula. The validation results show that themedia validity index is 0.76, which means that the level of feasibility is classified as feasible, the material validity index is 0.77, which means that the level of feasibility is classified as feasible, which indicates that the LKPD has good validity. After going through the validation process, the LKPD was tested on 36 students to measure its level of practicality. The test results show that the level of practicality of the LKPD reached 79.44%, which means that the level of practicalityis classified as practical. Based on theseresults, this LKPD is declared feasible to be used as a learning medium regarding buffer solutions at the high school level.